Intrinsically Ionic, Thermally Activated Delayed Fluorescent Materials for Efficient, Bright, and Stable Light‐Emitting Electrochemical Cells. (16th December 2021) - Yu, Renyou; Song, Yongjun; Zhang, Ke; Pang, Xianchun; Tian, Mingxing; He, Lei
Abstract: Solid‐state light‐emitting electrochemical cells (LECs) using sustainable and eco‐friendly materials and affording high brightness, efficiency, and stability are highly desired. Here, intrinsically ionic, thermally activated delayed fluorescence (TADF) materials 1–3 for efficient, bright, and stable LECs are reported. 1–3 feature carbazole‐type donors and cationic triazine‐type acceptors, which are located ortho to each other on the phenyl linkers. Through‐space charge‐transfer (CT) dominates the CT transitions in 1–3. In doped and neat films, 1–3 show blue and green TADF emission, respectively, with reverse intersystem crossing rates at around 7.0 × 10 5 s −1 . 1–3 possess excellent electrochemical stability (except for the oxidation of 1) and film‐forming abilities. LECs using neat films of 1–3 as the single active layers afford green electroluminescence with peak brightness/peak external quantum efficiency (EQE) of up to 572 cd m −2 /6.8% under 4.0 V and peak brightness/peak EQE/half‐lifetime of up to 860 cd m −2 /5.4%/48 h under 50 A m −2 . A longer half‐lifetime of 218 h has further been achieved at 162 cd m −2 under 10 A m −2 . The work reveals the bright prospect for the development of efficient, bright, and stable LECs with intrinsically‐ionic TADF materials. Abstract : Intrinsically ionic, thermally activated delayed fluorescence materials are developed with carbazole‐type donors and cationic triazine‐type acceptors, which enable solid‐state green light‐emitting electrochemical cells with a peak brightness/peak external quantum efficiency (EQE) of up to 572 cd m −2 /6.8% at 4.0 V and peak brightness/peak EQE/half‐lifetime of up to 860 cd m −2 /5.4%/48 h at 50 A m −2 .